IGF‐I attenuates FFA‐induced activation of JNK1 phosphorylation and TNFα expression in human subcutaneous preadipocytes - Neacsu, Otilia; Cleveland, Kelly; Xu, Haiyan; Tchkonia, Tamara T.; Kirkland, James L.; Boney, Charlotte M. (Obesity (Silver Spring, Md.), 2013)
Objective Free fatty acids (FFAs) are increased in visceral fat and contribute to insulin resistance through multiple mechanisms, including c‐Jun N‐terminal kinase (JNK) activation and expression of TNFα. Given that insulin‐like growth factor‐1 (IGF‐1)‐mediated proliferation is impaired in omental compared to subcutaneous (SC) preadipocytes, we investigated IGF‐I anti‐inflammatory action in preadipocytes from SC and omental adipose tissue. Design and Methods Preadipocytes isolated from abdominal SC and omental fat of obese subjects were studied in primary culture. Cells were exposed to FFAs with or without IGF‐I pretreatment followed by analysis of cytokine expression and JNK phosphorylation. Lentivirus infection was used to express a constitutively active AKT (myr‐AKT) in omental preadipocytes. Results FFAs increased the expression of tumor necrosis factor (TNF)α, interleukin (IL)‐6, and monocyte chemotactic protein (MCP)‐1 in SC and omental preadipocytes. IGF‐I pretreatment reduced FFA‐induced JNK1 phosphorylation and TNFα expression in SC but not omental preadipocytes. Treatment with the JNK1/2 inhibitor SP600125 reduced FFA‐induced expression of TNFα. FFAs and MALP‐2, a specific TLR2/6 ligand, but not specific ligands for TLR4 and TLR1/2, increased JNK1 phosphorylation. IGF‐I completely inhibited MALP‐2‐stimulated phosphorylation of JNK1. Expression of myr‐AKT in omental preadipocytes inhibited FFA‐stimulated JNK1 phosphorylation. Conclusions IGF‐I attenuated FFA‐induced JNK1 phosphorylation and TNFα expression through activation of AKT in human subcutaneous but not omental preadipocytes.